HIGH COURT OF ADMIRALTY PRIZE PAPERS, 1652-1815: CHALLENGES IN IMPROVING ACCESS TO OLDER RECORDS. Issue 137 (1st September 2018) - Bevan, Amanda; Cock, Randolph
Abstract : The prize papers of the high court of admiralty present multiple opportunities and challenges to researchers and archivists at the National Archives (TNA), where they have been held, almost unused, since the late 1850s. Increasing international academic interest in, and digitisation proposals for, this poorly-catalogued archive has led to the investment of scarce staff time by TNA. This is needed as part of the move from storing the papers according to the archival practices current in the 1650s–1850s, to delivering a collection ready for research and digitisation. The process presents a series of complex challenges which are explored here. After introducing a new project to digitise and describe all the prize papers, the paper covers the earlier archival and research responses to the collection; the use of the papers by the court; the development of a sorting practice for disarranged papers: and the reuniting of strays. The conclusion looks at the resource difficulties for funding this kind of work.